2021
DOI: 10.1029/2021ja029409
|View full text |Cite
|
Sign up to set email alerts
|

Ion Kappa Distribution Parameters in the Magnetosphere of the Earth at Geocentric Distances Smaller Than 20 RE During Quiet Geomagnetic Conditions

Abstract: From the very early studies of the Earth's magnetosphere, it became clear that particle flux spectra have energetic tails which are better described by power law distributions instead of exponential tails corresponding to Maxwell distributions. Given that the plasma density in the magnetosphere is very low, we are dealing with a collisionless plasma in which the relaxation of non-Maxwellian distributions toward Maxwellian distribution due to Coulomb collisions can take a long time. However, in spite of the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 63 publications
4
12
0
Order By: Relevance
“…We were also able to capture the crescent-like region (near 𝐴𝐴 𝐴𝐴∼ 10𝐴𝐴e ), as described by Kirpichev et al (2021), who showed its existence in the dusk, midnight, and dawn sectors where the protons are thermalized, and the kappa index can reach values of ∼10 (see Figure 4 of their paper). However, deviations are also found at some locations, especially in the averaged 𝐴𝐴 𝐴𝐴 values, which could be explained by (a) spatio-temporal averaging of 𝐴𝐴 𝐴𝐴RCM , (b) fitting the protons' spectrum with a two-functional form (i.e., Maxwellian plus kappa), (c) using Geotail data as the RCM boundary particle distribution, (d) different complex processes (e.g., wave-particle/wave interactions and loss), and (e) different temporal averaging.…”
Section: Spectral Characteristicsmentioning
confidence: 61%
See 3 more Smart Citations
“…We were also able to capture the crescent-like region (near 𝐴𝐴 𝐴𝐴∼ 10𝐴𝐴e ), as described by Kirpichev et al (2021), who showed its existence in the dusk, midnight, and dawn sectors where the protons are thermalized, and the kappa index can reach values of ∼10 (see Figure 4 of their paper). However, deviations are also found at some locations, especially in the averaged 𝐴𝐴 𝐴𝐴 values, which could be explained by (a) spatio-temporal averaging of 𝐴𝐴 𝐴𝐴RCM , (b) fitting the protons' spectrum with a two-functional form (i.e., Maxwellian plus kappa), (c) using Geotail data as the RCM boundary particle distribution, (d) different complex processes (e.g., wave-particle/wave interactions and loss), and (e) different temporal averaging.…”
Section: Spectral Characteristicsmentioning
confidence: 61%
“…By fitting THEMIS satellite data during geomagnetically quiet conditions to a single kappa distribution function, Kirpichev et al. (2021) obtained the equatorial distribution of proton kappa parameters (κp ${\kappa }_{\mathrm{p}}$) to elucidate plasma heating and acceleration processes. They discovered that κp ${\kappa }_{\mathrm{p}}$ peaks in an arc‐like region between 8 $8$ and 10Re $10{R}_{\mathrm{e}}$ in the dawn, night, and dusk, presumably due to insignificant impact of injections.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we used a modified version of that method, which was proposed by Stepanova et al (2006). The ion pressure is calculated under the assumption of a Maxwellian energy distribution of particles, which, despite the recorded non Maxwellian energetic tails of the distribution functions, does not lead to significant errors in calculating the pressure in the considered regions (Kirpichev et al, 2021). To avoid a significant effect of substorm processes on the results of the study, an important criterion in selecting the data and study intervals was the low level of magnetic activity in the auroral zone, AL > -200 nT.…”
Section: The Datamentioning
confidence: 99%